2014
DOI: 10.1111/jvp.12155
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of amoxicillin trihydrate in cultured olive flounder (Paralichthys olivaceus)

Abstract: The study was aimed at investigating the pharmacokinetics of amoxicillin trihydrate (AMOX) in olive flounder (Paralichthys olivaceus) following oral, intramuscular, and intravenous administration, using high-performance liquid chromatography following. The maximum plasma concentration (Cmax ), following oral administration of 40 and 80 mg/kg body weight (b.w.), AMOX was 1.14 (Tmax , 1.7 h) and 0.76 μg/mL (Tmax , 1.6 h), respectively. Intramuscular administration of 30 and 60 mg/kg of AMOX resulted in Cmax valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Parenteral administration of drugs in culture fish is mostly limited to specific agents like vaccines, reproduction controllers or anaesthetics due to technical difficulty and high labour costs (Black, 2000). In recent years, however, the application of some injectable drugs has been found feasible when they were administered intramuscularly in Korean culture farms, particularly for olive flounder (Lee & Park, 2015; Lim et al., 2017; Seo et al., 2015). This fish species is generally calm and can easily be handled without excess stress during injections.…”
Section: Discussionmentioning
confidence: 99%
“…Parenteral administration of drugs in culture fish is mostly limited to specific agents like vaccines, reproduction controllers or anaesthetics due to technical difficulty and high labour costs (Black, 2000). In recent years, however, the application of some injectable drugs has been found feasible when they were administered intramuscularly in Korean culture farms, particularly for olive flounder (Lee & Park, 2015; Lim et al., 2017; Seo et al., 2015). This fish species is generally calm and can easily be handled without excess stress during injections.…”
Section: Discussionmentioning
confidence: 99%
“…However, Seo et al . () reported that a two‐compartment model best represented the relationship between plasma concentration and the time after i.m. administration of amoxicillin trihydrate in olive flounder.…”
Section: Discussionmentioning
confidence: 99%
“…Seo et al . () reported the pharmacokinetics of amoxicillin trihydrate in olive flounder following oral, i.m., and intravenous (i.v.) administrations.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceutics 2023, 15, 1153 2 of 8 Seo et al [6] determined the PK of AMOX in olive flounder after a single IM injection of trihydrate salt.…”
Section: Introductionmentioning
confidence: 99%